Methodological Basis for Shaping Metrics of Strategic Management by the Enterprise in View of Low-Carbon Economy Concept - Е. S. Lobova; L. N. Mamaeva (Вестник Российского экономического университета имени Г. В. Плеханова)
The concept of sustainable development is still one of the most topical and debatable. To attain goals set at the UN conference is an objective of the adequate strategic planning in the enterprise work. For enterprises functioning in complicated multi-level social and economic systems this aim requires a new look at the system of indicators. The article studies the system of strategic management of gas industry enterprises. The goal of the research is to build a methodological foundation necessary to implement the concept of green economy in metrics of strategic management of the enterprise. In the process of attaining the set goal the following tasks were resolved: to review key lines of implementing the concept of sustainable development, to substantiate the choice of the green economy concept as a methodological foundation for strategic planning at the gas industry enterprise, by using the correlation analysis to identify the principle indicators of evaluating effectiveness of strategic management. The authors substantiated the use of the green economy concept in the context of setting goals for the low-carbon development of the country. The indicators of estimating ecological effectiveness were adapted to characteristics of sectoral production, the system of social-ecologic and economic indicators was devised, which can be used as indicators of reaching goals of sustainable development in line with strategic planning of the enterprise work.